(untitled) (International Association of Biologicals and Computational Digest, 2023)
This study contributes to a better understanding of Grangea maderaspatana (L) Poir. a species of the Asteraceae family, as a pharmaceutical plant for its phytochemicals. Extracts from leaves analysed for phytochemicals. Methanol and hexane were used to prepare the extracts from the leaf. Spectrophotometric techniques were used to determine the total phenolics, total flavonoids, total tannin and total antioxidants contents. The phytochemical screening was also carried out by means of thin layer chromatography.